Pengaruh Perbedaan Ketebalan Irisan Asam Gelugur (Garcinia atroviridis) Terhadap Kandungan Total Asam Pada Asam Sitrat Dengan Pengeringan Sinar Matahari Sistim Konveksi Paksa - Parulian Siagian; Tumiur Gultom; Sibuk Ginting; Hotman Manurung; Eko Y Setyawan (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2019)
The mechanism of the drying process is the process of heat transfer and mass transfer that takes place simultaneously. The pressure of the water vapor in the acid gelugur is higher than that on the surface interface of the gums and air acids. Intensity solar radiation averages around 300-590w / m2 and Ambient Temperature 28,830C. The hot air condition in the drying box averages 320C. The content of total citric acid gelugur acid was 1.2787% with 3mm slice thickness and 1.3981% with a 5mm slice thickness. Drying is done from 08.00-17.00 am with a hot air flow rate of 1.5m/s.